PENGARUH PENERAPAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP CIVIC KNOWLEDGE SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V UPT SDN 25 MENGKENDEK KABUPATEN TANA TORAJA - Nurfaizah AP; Muh.Faisal; Fauziah Magfirah Ramadhani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low civic knowledge of students in Civics learning is the background for conducting research to determine the application of the Value Clarification Technique (VCT) model to student civic knowledge. This research aims to: (1) to know the application of the VCT model to students' civic knowledge in Civics learning, to know the application of students' civic knowledge results in Civics learning, and to describe the effect of the VCT model on the civic knowledge of grade V students of UPT SDN 25 Mengkendek. The approach used in this research is quantitative with the type of Quasi Experimental type Non-equivalent Control Group Design. The population in this study amounted to 38 students. Data analysis techniques used are descriptive statistical analysis and inferential statistics. The results of descriptive analysis showed that the application of the VCT model went very well. The results of inferential analysis using Independent Sample t-Test showed that the t.count value was greater than the t.table value with a predetermined significance level, so the alternative hypothesis was accepted and the null hypothesis was rejected. Based on the research results, it can be concluded that: (1) the learning process using the VCT model takes place very well, (2) the learning outcomes of students' civic knowlede show a very high influence on Civics learning, (3) and there is an effect of using the VCT model on the civic knowledge of grade V UPT SDN 25 Mengkendek Tana Toraja Regency.